Electroencephalographic differences between WAG/Rij and GAERS rat models of absence epilepsy - ONAT, FİLİZ (ELSEVIER, 2010)
The inbred Wistar Albino Glaxo Rats from Rijswijk (WAG/Rij) and the Genetic Absence Epilepsy Rats from Strasbourg (GAERS) are well-validated genetic models of absence epilepsy. Although they share similar characteristics including the spike-and-wave discharges (SWDs) in the EEG, some differences have been reported between both strains. This study aimed a systematic and detailed comparison of the SWD patterns of both strains in terms of the intensity, frequency and waveform morphology of the discharges by using exactly the same measurement and analysis techniques. The number, cumulative total duration and mean duration of SWDs were significantly higher in GAERS compared to WAG/Rij, while the discharge frequency was higher in the WAG/Rij. Furthermore, SWDs spectra and average SWD waveforms indicated that a single cycle of the SWD contains more energy in faster components such as spike and late positive transient in the GAERS. Additionally, WAG/Rij exhibited a significantly higher power between 8 and 14 Hz during the pre-SWD period. These clear phenomenological differences in the EEGs of both animal models suggest that these variables may represent basic phenotypic features of SWDs that should be sought after in the future studies that explore the genetic and molecular basis of absence epilepsy. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: WAG/Rij; GAERS; Spike-and-wave discharges; Power spectrum; Frequency domain; Waveform morphology; SPIKE-WAVE DISCHARGES; IDIOPATHIC GENERALIZED EPILEPSY; GENETIC MODEL; SEIZURES; EEG; MECHANISMS; PHENOTYPES; THALAMUS; STRAIN